Early Experience of Endovascular Repair of Post-dissection Aneurysms Involving the Thoraco-abdominal Aorta and the Arch. Issue 4 (April 2016) - Spear, R.; Sobocinski, J.; Settembre, N.; Tyrrell, M.R.; Malikov, S.; Maurel, B.; Haulon, S.
Abstract : Objectives: Outcomes are reported in management of post-dissection aneurysms involving the aortic arch and/or thoraco-abdominal segment (TAAA) treated with fenestrated and branched (complex) endografts. Methods: This report includes all patients with chronic post-dissection aneurysms >55 mm in diameter, deemed unfit for open surgery, treated using complex endografts between October 2011 and March 2015. When appropriate, staged management strategies including left subclavian artery revascularization, thoracic endografting, dissection flap fenestration or tear enlargement, and other endovascular procedures were performed at least 3 weeks prior to definitive complex endovascular repair. The following outcome data were collected prospectively at discharge, 12 months and annually thereafter: technical success, endoleaks, target vessel patency, false lumen patency, aneurysm diameter, major and minor complications, re-interventions, and mortality. Results: The cohort comprised 23 patients with a median age of 65 years. Staged procedures were performed in 14 patients (61%). Seven patients with dissections involving the arch were treated with inner branched endografts, and 16 TAAA patients were treated with fenestrated or branched endografts. The technical success rate was 71% following arch repair and 100% following TAAA repair. During early follow up, one of the arch group patients died and one in the TAAA group suffered spinal cord ischemia. The median follow up was 12 months (range 3–48), during which time one patient died of causes unrelated to aneurysm or treatment. Two early re-interventions were performed in the arch group to correct access vessel complications and there were a further two late re-interventions in the TAAA group to treat endoleaks. All target vessels ( n  = 72) remained patent. Conclusions: This experience indicates that complex endovascular repair of post-dissection aneurysms is a viable alternative to open repair in patients deemed unfit for open surgery. There are insufficient data to allow comparison with the outcome of open surgery in anatomically similar, but fit, patients.